ANALISIS PENGARUH KUALITAS SISTEM LAYANAN, LINGKUNGAN FISIK JASA, PERSONIL KONTAK, NILAI UTILITARIAN, DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PENGGUNA BRT TRANS SEMARANG) - Trisnawati, Debora; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2018)
This study aims to explain the influence of service system quality, service environment, and contact personnel in order to influence purchasing decision, which utilitarian value and corporate image are used as intervening variables between service system quality, service environment, and contact personnel to BRT Trans Semarang customer’s purchasing decision.Sampling of this research was done by using a non-probability sampling with purposive sampling method, in which respondents is BRT Trans Semarang. The answers of 175 respondents were analyzed using Statistical Package for Social Science (SPSS) 22 with  Multiple Regressional Analysis as analytical tool. The first regression to analyze the effect of service system quality on utilitarian value. The second regression to analyze the effect of service environment and contact personnel on corporate image. While, the third regression to analyze the effect of utilitarian value and corporate image on purchase decision. The result shows that service system quality has positive and significant impact on utilitarian value. Service environment and contact personnel have positive and significant impact on corporate image. Utilitarian value and citra perusahaan also have positive and significant impact on purchasing decision.This study aims to explain the influence of service system quality, service environment, and contact personnel in order to influence purchasing decision, which utilitarian value and corporate image are used as intervening variables between service system quality, service environment, and contact personnel to BRT Trans Semarang customer’s purchasing decision.Sampling of this research was done by using a non-probability sampling with purposive sampling method, in which respondents is BRT Trans Semarang. The answers of 175 respondents were analyzed using Statistical Package for Social Science (SPSS) 22 with  Multiple Regressional Analysis as analytical tool. The first regression to analyze the effect of service system quality on utilitarian value. The second regression to analyze the effect of service environment and contact personnel on corporate image. While, the third regression to analyze the effect of utilitarian value and corporate image on purchase decision. The result shows that service system quality has positive and significant impact on utilitarian value. Service environment and contact personnel have positive and significant impact on corporate image. Utilitarian value and citra perusahaan also have positive and significant impact on purchasing decision.